Briefwechsel Oktober 1745 - September 1746 - Gottsched, Johann Christoph (Briefwechsel, 2017)
In this volume, Gottsched speaks in detail about the tangible impacts of Prussia`s defeat of the Electorate of Saxony. Letters also describe Gottsched`s work for the 1746 Luther and Leibniz prizes and the gifts to the local Alethophile Society. Along with Gottsched`s contacts with playwrights, drama collecting, and critical activity, the letters reveal the beginnings of his quest for medieval German poetry manuscripts.